Environmental Education in the “City of Foundries”: public policies and the configuration of environmental racism (Research, Society and Development, 2021)
The city of Aperibé, in the state of Rio de Janeiro, concentrates a population and territorial dimension that places it in the socio-spatial category, called by the IBGE, “small center”. However, in that same city, the quantity of metallurgical foundry industries has grown significantly and, consequently, the environmental impacts of this economic activity. Given this reality, we propose this research that aims to: analyze the implementation of public environmental policies in the city of Aperibé-RJ, especially Law N. 9795, of April 27, 1999 – National Policy for Environmental Education. Methodologically, we adopted a qualitative research approach, using semi-structured interviews as a data collection instrument. Four municipal managers participated in the research, linked to the following Municipal Offices: Department of Education, Department of Environment and Department of Budget Infrastructure. The research data were analyzed from the methodological perspective of discourse analysis, covering three analytical categories: a) environmental problems – perceptions of municipal managers; b) foundry – operation of industries and generation of employment and income; c) Environmental Education – actions and projects developed. The main results indicate that the representatives of the secretariats did not consider the foundries as providers of environmental impacts. Moreover, many of the metallurgical plants in operation do not meet the standards of environmental protection and individual safety of workers. Furthermore, the results highlight the existence of few Environmental Education projects and the inexistence of aspects that discuss the environmental impacts caused by the foundry sector.